Knowledge and practice on proper disposal of radiographic wastes of dentists in Malate a pilot study - Cayabyab, Minionette; Dizon, Ethel C.; Atienza, Charleton (Adviser).
Proper disposal of radiographic waste is equally important to following infection control protocols upon taking oral radiographs. The radiographic wastes potentially hazardous to the environment and the community per se are lead foil and silver crystals. This descriptive study examined the knowledge and practice of dentists regarding proper disposal of radiographic wastes. More specifically, this research was able to: (1) determine the knowledge of dentists regarding identification, toxicity and proper disposal of radiographic film, developing solution, fixing solution, and rinse water; (2) to evaluate whether respondents follow proper segregation of film parts and proper disposal of radiographic wastes; and (3) to identify the sources where they acquire their knowledge on radiographic wastes' disposal and toxicity. Forty (40) dentists practicing in Malate cooperated in answering a survey form which is divided into two parts: (1) evaluation of knowledge in accordance to the said topic; and (2) determination of the manner by which they dispose their radiographic wastes. This study concludes that only 5% of the respondents are knowledgeable regarding identification, toxicity, and proper disposal of radiographic wastes and they practice improper disposal of radiographic wastes except for the developing solution.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Infection Control, Dental; Dental waste; Hazardous substances